2000
DOI: 10.1001/archsurg.135.9.1055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Esophageal Bougie on the Incidence of Dysphagia Following Nissen Fundoplication

Abstract: Based on retrospective, uncontrolled studies, it has been claimed that Nissen fundoplication should be performed over an esophageal bougie to minimize postoperative dysphagia. We hypothesized that a surgeon experienced in laparoscopic fundoplication will have similar rates of postoperative dysphagia whether or not an esophageal bougie is used. Design: A patient and observer blinded, randomized, prospective clinical trial to assess the effect of intraoperative bougie use. Setting: A tertiary care teaching hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(70 citation statements)
references
References 30 publications
4
64
0
2
Order By: Relevance
“…DeMeester et al 4 proposed the use of large tube (48-50FR) inside the esophagus for calibration of the fundoplication to prevent transitory dysphagia. These fi ndings were similar to the results of Patterson et al 29 . Some authors advocate no advantages by this routine technique 30 , emphasizing the risk for perforation and severe complications related to these tubes 29,31 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…DeMeester et al 4 proposed the use of large tube (48-50FR) inside the esophagus for calibration of the fundoplication to prevent transitory dysphagia. These fi ndings were similar to the results of Patterson et al 29 . Some authors advocate no advantages by this routine technique 30 , emphasizing the risk for perforation and severe complications related to these tubes 29,31 .…”
Section: Discussionsupporting
confidence: 92%
“…These fi ndings were similar to the results of Patterson et al 29 . Some authors advocate no advantages by this routine technique 30 , emphasizing the risk for perforation and severe complications related to these tubes 29,31 . We do not use this tube, but we double-check the gastric fundus fl oppy anti-refl ux valve as described previously.…”
Section: Discussionsupporting
confidence: 92%
“…111,112 Some authors, therefore, do not recommend its routine use. 113 Looking at the only available RCT, 72 it appears that routine use of a bougie significantly reduces the rate of severe postoperative dysphagia, as defined by the authors, by 13.7%, with a 1.2% risk of iatrogenic perforation (Table 10). On the other hand, if we look at something more clinically relevant, such as the rate of postoperative dilatation, the results were higher in the group treated by routine use of the bougie.…”
Section: Hiatoplasty and Calibrationmentioning
confidence: 99%
“…71 Concerning calibration of hiatoplasty and wrapping by means of an esophageal bougie, there was 1 trial from Portland, Oregon. 72 The details and results of these trials are shown in Table 10.…”
Section: Hiatoplasty and Calibrationmentioning
confidence: 99%
“…RCTs comparing total fundoplication with and without division of short gastric vessels can not show any statistically significant difference in the outcome dysphagia (11) . The use of intraesophageal bougies and the confection of a floppy and short valve seems to be effective in reduce dysphagia (8,26) , but there are not much trials with methodological quality to confirm theses hypothesis.…”
Section: Discussionmentioning
confidence: 98%